Exonuclease III recognizes urea residues in oxidized DNA. - Kow, Y W (1985)
Escherichia coli exonuclease III was found to be associated with an activity that recognizes urea residues in DNA but not thymine glycol residues from which the urea residues were prepared. This activity was not due to a contaminating activity such as endonuclease III since urea-containing DNA was a competitive inhibitor of exonuclease III when apurinic DNA was used as a substrate and vice versa. The apparent kinetic constants for both the substrate and inhibitor were determined. Like its apurinic activity, exonuclease III activity against urea residues was endonucleolytic, nicking on the 5' side of the damage and having an optimal Mg2+ concentration between 2 and 10 mM. Also, the enzyme recognized alkali-stable damages produced in DNA by H2O2 in vitro. We suggest that it may be this activity of exonuclease III that accounts for its biological role in vivo.